Body, quotidian, image, and creation: research and schools - Victorio Filho, Aldo (2019)
In this article, we depart from the notion that the poetic dimension and aesthetic assemblages, which fail to meet the categorical limits of the arts in which they are energy and immanence, spread, cross and envelop daily practices, standing out in the fields where creative actions reach more evident relief, such as caring for oneself simultaneously with the invention of the world, situations that both individually and collectively are the bone and flesh of the school life. When we consider the affirmation of the body beyond what modernity has considered and exiled, we perceive it as a self-creative dimension, both individually and collectively, as each body assimilates, creates and shares experiences in the social interactions conducted by the imaginary symbolic dimensions.